A Positioning Map and Future Research Agenda of Collaborative Consumption - Damayanti Octavia; Gatot Yudoko; Reza Ashari Nasution (Jurnal Sosial Humaniora, 2020)
Collaborative consumption (CC) is the new business model which overlapswith the concept of sharing economy (SE). However, CC has some uniquecharacteristics that are not found in SE. This study aims to compare the twobased on three dimensions: compensation, ownership, and platform. ECommerce (EC) is included into the comparison in order to show that CC isactually a combination of SE and EC, thus covering a larger set than the othertwo concepts. The method used in this study is the literature study. Themethods used CC concept manually and VOSviewer software to reassure andexplore the unique characteristics of CC in comparison with SE and EC. Thepositioning map based on two dimensions: compensation and platformgenerate six business models that can be represented the characteristic of CC,SE, and EC. The six models are: (1) platform-based and monetarycompensation; (2) platform-based and non-monetary compensation; (3)platform-based and without compensation; (4) non-platform-based andmonetary compensation; (5) non-platform-based and non-monetarycompensation; (6) non-platform-based and without compensation. The lastdimension is ownership describe that CC activity is including exchange-basedand access-based activity, while SE provides access-based activity only andEC offering exchange-based activity. The study also aims to discover theunique characteristics of CC that will be used as the basis for developing afuture research agenda of CC.